Rapid on-the-spot detection of Edwardsiella piscicida using recombinase polymerase amplification with lateral flow - Jiatiao Jiang (Elsevier, 2022)
Edwardsiella piscicida is one of the important pathogens in aquaculture, which takes huge losses to the economic benefits of turbot industry. Thus, a simple, rapid and accurate diagnostic assay of E. piscicida becomes an urgent need. In the present study, a detection method of E. piscicida based on recombinase polymerase amplification combined with lateral flow strip (RPA-LF) was established. The RPA-LF assay targeted E. piscicida evpP gene and could detect as low as 10 fg DNA of E. piscicida, which was approximately 1000 times more sensitive than conventional PCR assay. Meanwhile, the RPA-LF assay showed no cross-reactivity with DNA from other major bacterial pathogens in aquaculture. Besides, to improve the convenience of RPA-LF assay, a rapid on-the-spot sample preparation using nucleic acid extraction by cellulose dipsticks was established. Results indicated that bacteria could be detected as low as 1 copy and completed within 30 min. Moreover, this modified RPA-LF assay could be used to monitor E. piscicida infection in turbot industry.